การศึกษาสภาพและปัญหาการบริหารโรงเรียนอนุบาลเอกชนสองภาษา สังกัดสำนักบริหารงานคณะกรรมการส่งเสริมการศึกษาเอกชนในกรุงเทพมหานคร - สิทธิ์ จิตต์นิลวงศ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
To study the state and problems of the administration of Bilingual private kindergartens under the Office of the Private Education Commission in Metropolitan Bangkok. The responders of the questionnaires were 42 School administrators and 186 Thai teachers. The research tool was questionnaire. Data were analyzed by frequencies and percentage and were presented in tables and description. The research findings were as follows: 1. State of Academic Administration : there has been using English Program of Ministry of Education, determining annual plan, lesson plans determined by Thai teachers and Foreign teachers, evaluation at the end of each semester, teacher development program by supervision and the extra activity program organize from contents of curriculum structure. Problems : the school personnel’s lack of knowledge and clear understanding in bilingual curriculum, the objective were not determined clearly, there were not provided with proper training course of lesson plans, the instructional material and teaching equipment were not enough for students need, higher educate of teacher lack of supporting form administrator and a school administrator was not assigned person who in charge of the extra activity program. 2. State of Personnel Administration : the criteria for foreign teachers to be mainly considered is a native speaker, teachers were clear understanding in job objective before implementation, there were internal supervision and quality of success works were considered by formative evaluation. Problems : foreign teachers were at high a turn over rate, education background of teacher did not match the school criteria and there was an inadequacy in teacher development programs. 3. State of Community and public relations administration : the verbal or written documents form opinion of guardian were done in small group meeting, there were printing materials, entertainment and school plant facility were used for the participation in developing and servicing the community. Problems : a school administrator did not assigned person who was in charge of such a task. 4. State of Building and premises administration : school plant was constructed for a kindergarten, premised room equipments such as writing tables and chairs, cabinets were ready for use. Problems : size and space were unsuitable for the number of students. 5. State of Student personnel administration : English and Thai subject were extra instruction in school. Additional important day was provided apart of student activities and lunch service for students. Problems : a school administrator did not assigned person in charge of them and the school personnel’s lack of knowledge and clear understanding in creating activities.